Balancing the moments produced by a variably loaded crank - Stokely, Charles H. (My University, 1897)
Introduction: A variably loaded crank is one that is loaded and relieved at certain intervals of its path of rotation. A good example of one is a hay press, or _____ pump crank. A moment is the measure of a tendency of a force to rotate about a fixed point. It is the product of the force into the perpendicular distance from the point of rotation to the line in the direction of the acting force.
Citation: Stokely, Charles H. Balancing the moments produced by a variably loaded crank. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Mechanical engineering; Variably loaded crank; Hay press; Pump crank; Theses; Manuscripts (documents)